ANALISIS PENGARUH PENGGUNAAN DUA NOZZLE TERHADAP DAYA OUTPUT LISTRIK PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA PIKOHIDRO DENGAN MENGGUNAKAN TURBIN TURGO - Yoga Pratama, I.G.; Arta Wijaya, I.W.; Budiastra, I.N. (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p11, 2023)
This study uses two nozzles on the PLTPH prototype with a turgo turbine because this research wants to apply the use of two nozzles in a pelton turbine. This study aims to determine the effect of using two nozzles on the output power produced by the PLTPH prototype with the direct test method on the prototype made. This two-nozzle PLTPH prototype with a turgo turbine can produce higher turbine rotation than the existing conditions. The final result is the highest rotation on the turbine using 2 nozzles where the A nozzle angle is 70° based on the x axis and the B nozzle angle is 60° based on the y axis of 752.2 rpm. In the 4:1 gear ratio transmission test, the results obtained were 504.4 rpm turbine rotation, 2114.9 rpm generator rotation, 10.99 volt voltage, 4.43 amperes current, and 48.70 watt power.